ИХ, ДЭЭД СУРГУУЛИЙН УЛС ТӨР СУДЛАЛ ХИЧЭЭЛИЙН ӨНӨӨГИЙН БАЙДЛЫН ШИНЖИЛГЭЭ - Д.Одмаа (Politology, 2023)
The paper mentions about how to held political training in non-majoring classes, its feature and what we should focus on in the future. Today, the credit for the political training is not assorted. For instance every university changes their credit, seminar, lecture hours as they want. And also many universities have more part-time lecturer. The lecturers formulate their lesson plan by themselves. And they have different kind of lesson content and curriculum. Therefore we conducted a survey including 13 universities, 58 institutes, 5 foreign domestic schools. Survey result showed that each school has their own plan and follow them. To determine the issues above, find out the good way and analyze. So it influences not only bad effect for the quality of lesson, but also students can’t get proper knowledge about politics.